Improving the fracture property of polymer nanocomposites by employing nanoparticles as cross-linking points. (1st October 2020) - Mu, Guangyao; Li, Haoxiang; Sun, Wei; Wu, Haoyu; Luo, Yanlong; Gao, Yangyang; Zhao, Xiuying; Zhang, Liqun
Graphical abstract: Highlights: The fracture property of polymer nanocomposites is investigated by employing NPs as cross-linking points. More bonds are broken on the chain backbone while the percentage of broken bonds is larger between chains and NPs. By quantifying the stress contribution, the high stress is borne by one NP or one end bead than one non-end bead of chains. The nucleation position and the evolution process of voids and bond scission are characterized. Abstract: In this work, a coarse-grained molecular dynamics simulation is performed to construct the end-linked polymer nanocomposites (PNCs) by employing the nanoparticles (NPs) as cross-linking points where the dual end beads of chains are bonded on the surface of NPs. The evolution process of the bond scission and voids is analyzed to understand the effect of the end-grafting density, the chain length, and their polydispersity index (PDI) on the fracture property of the end-linked PNCs. The fracture energy first rises and then declines with the end-grafting density or the chain length while it is gradually reduced with the PDI. It is observed that the number of broken bonds on the chain backbone is more than that between chains and NPs which is related to their number. On the contrary, the percentage of broken bonds between chains and NPs is larger than on the chain backbone due to the high stress by one NP or one end bead. Meanwhile, the percentage of broken bonds is larger on the short chains than on the long chains. Moreover, the number of voids first rises and then decreases with the strain. The following increase is attributed to the new formed voids which is induced by the broken bonds. This can be proved by that the strain at the second rise of number of voids is roughly similar to that at the beginning of bond scission. In summary, our results help to design and fabricate the end-linked PNCs with high fracture property which can facilitate their potentially application.